Bendamustine for patients with indolent B cell lymphoproliferative malignancies including chronic lymphocytic leukaemia – an updated meta‐analysis. (13th April 2019) - Vidal, Liat; Gurion, Ronit; Shargian, Liat; Dreyling, Martin; Gafter‐Gvili, Anat
Summary: The question of which chemotherapy induction provides the best results for indolent lymphoma patients is yet unanswered. Different regimens have been compared, none of which has been shown to improve overall survival. The use of bendamustine is growing. A number of trials evaluated its efficacy for patients with indolent B‐cell lymphoid neoplasms, including chronic lymphocytic leukaemia (CLL). To evaluate the efficacy of bendamustine in that population we performed a systematic review and meta‐analysis of 9 randomised controlled trials (2726 patients). Bendamustine was compared to fludarabine‐containing regimens, CVP (cyclophosphamide, vincristine, prednisolone), CHOP (CVP+ doxorubicin) and chlorambucil. Due to insufficient reported data, six of the nine trials were included in analysis of overall survival. Bendamustine was associated with a prolonged overall survival, (hazard ratio 0·79, 95% confidence interval 0·65–0·95). Data regarding quality of life was reported for two trials, therefore too scarce to pool. The risk of neutropenia was reduced with bendamustine treatment compared to other chemotherapy. Bendamustine induction is an efficacious option for patients with indolent lymphoma, and CLL. Maintenance therapy was not evaluated after bendamustine induction, and potentially there is an interaction between the two. Chemotherapy‐free approach was shown to be efficacious for patients with CLL, while toxicity with that approach is not negligible.